Cannabidiol regulation of extinction and relapse of learned fear - Papagianni, Eleni (2023)
Anxiety- and trauma-related disorders are chronic debilitating mental conditions, characterized by dysregulation of aversive memory processing and its impaired suppression. Current pharmacological and exposure-based psychotherapeutic approaches often produce inadequate responses, resulting in elevated rates of relapse. Cannabidiol (CBD), the non-psychotropic constituent of Cannabis Sativa, demonstrates a promising therapeutic potential for these disorders due to its modulating effects on the expression and extinction of learned fear.